Local Culture–Based Dance Learning with the Integration of Students’ Creativity, Motor Skills, and Social Sensitivity - Nury astuti, Fitri aji; Malarsih Malarsih; Slamet Haryono; Widodo Widodo (Catharsis, 2025)
Indonesia’s cultural wealth encompasses a wide range of ethnic groups and traditions, including traditional dances that uniquely represent the history, values, and daily lives of local communities. However, in the current era of technological advancement and globalization, traditional dance faces significant challenges, particularly a decline in cultural awareness among younger generations, which has resulted in decreasing interest in cultural heritage. The limited number of studies examining local culture–based dance learning models that integrate creativity, motor skills, and social sensitivity has prompted this study to further explore the implementation of local culture–based dance education as a strategy for preserving cultural heritage while simultaneously fostering students’ creativity, motor development, and social competencies. This article employs a qualitative research approach through literature review, observation, interviews, and documentation conducted in several senior high schools in Pemalang Regency. The findings indicate that local culture–based learning not only contributes to the preservation of traditional dance but also enhances students’ appreciation of their cultural identity. Instructional methods such as demonstration, participatory learning, creative exploration, case studies, and collaborative projects were identified as effective pedagogical approaches. Furthermore, strategies including collaboration with local artists, curriculum integration, and the utilization of technology were found to enrich learning outcomes. Local culture–based dance education plays a crucial role in shaping culturally aware, creative young generations with strong social skills. This approach serves as a bridge connecting young people to their cultural roots, ensuring that traditional arts remain vibrant amid modernization while simultaneously strengthening cultural identity.